The translational value of calcium pyrophosphate deposition disease experimental mouse models - Luisetto, Roberto; Scanu, Anna (Frontiers in Medicine, 2024)
The deposition of calcium pyrophosphate (CPP) crystals in joint tissues causes acute and chronic arthritis that commonly affect the adult and elderly population. Experimental calcium pyrophosphate deposition disease (CPPD) models are divided into genetically modified models and crystal-induced inflammation models. The former do not reproduce phenotypes overlapping with the human disease, while in the latter, the direct injection of crystals into the ankles, dorsal air pouch or peritoneum constitutes a useful and reliable methodology that resembles the CPP induced-inflammatory condition in humans. The translational importance of the induced model is also strengthened by the fact that the key molecular and cellular mediators involved in inflammation are shared between humans and laboratory rodents. Although, in vivo models are indispensable tools for studying the pathogenesis of the CPPD and testing new therapies, their development is still at an early stage and major efforts are needed to address this issue. Here, we analyze the strenghts and limitations of each currently available CPPD in vivo model, and critically discuss their translational value.